Atomically‐Precise Texturing of Hexagonal Boron Nitride Nanostripes. Issue 17 (22nd July 2021) - Ali, Khadiza; Fernández, Laura; Kherelden, Mohammad A.; Makarova, Anna A.; Píš, Igor; Bondino, Federica; Lawrence, James; de Oteyza, Dimas G.; Usachov, Dmitry Yu.; Vyalikh, Denis V.; García de Abajo, F. Javier; El‐Fattah, Zakaria M. Abd; et al.
Abstract: Monolayer hexagonal boron nitride (hBN) is attracting considerable attention because of its potential applications in areas such as nano‐ and opto‐electronics, quantum optics and nanomagnetism. However, the implementation of such functional hBN demands precise lateral nanostructuration and integration with other two‐dimensional materials, and hence, novel routes of synthesis beyond exfoliation. Here, a disruptive approach is demonstrated, namely, imprinting the lateral pattern of an atomically stepped one‐dimensional template into a hBN monolayer. Specifically, hBN is epitaxially grown on vicinal Rhodium (Rh) surfaces using a Rh curved crystal for a systematic exploration, which produces a periodically textured, nanostriped hBN carpet that coats Rh(111)‐oriented terraces and lattice‐matched Rh(337) facets with tunable width. The electronic structure reveals a nanoscale periodic modulation of the hBN atomic potential that leads to an effective lateral semiconductor multi‐stripe. The potential of such atomically thin hBN heterostructure for future applications is discussed. Abstract : Vapor growth of borazine on a curved Rh surface leads to continuous hexagonal boron nitride (hBN) monolayer coating, under which nanomesh‐quantized Rh(111) terraces and stepped Rh(337) facets segregate, The latter reveals a perfect hBN/Rh interface registry, with all N atoms anchoring at step on‐top positions. This imprints a strong uniaxial anisotropy in the electronic band structure of the hBN monolayer.